Contribution of membrane transporters to chemotherapy‐induced cardiotoxicity. (21st July 2021) - Uddin, Muhammad Erfan; Moseley, Angie; Hu, Shuiying; Sparreboom, Alex
Abstract: Membrane transporters play a key role in determining the pharmacokinetic profile, therapeutic safety, and efficacy of many chemotherapeutic drugs by regulating cellular influx and efflux. Rapidly emerging evidence has shown that tissue‐specific expression of transporters contributes to local drug accumulation and drug–drug interactions and that functional alterations in these transporters can directly influence an individual's susceptibility to drug‐induced toxicity. Comprehending the complex mechanism of transporter function in regulating drug distribution in tissues, such as the heart, is necessary in order to acquire novel therapeutic strategies aimed at evading unwanted drug accumulation and toxicities and to ameliorate the safety of current therapeutic regimens. Here, we provide an overview of membrane transporters with a role in chemotherapy‐induced cardiotoxicity and discuss novel strategies to improve therapeutic outcomes.